Chemical Composition and in vitro Biological Activities of the Essential Oil of Vepris macrophylla (Baker) I.Verd. Endemic to Madagascar. Issue 3 (13th March 2013) - Maggi, Filippo; Fortuné Randriana, Richard; Rasoanaivo, Philippe; Nicoletti, Marcello; Quassinti, Luana; Bramucci, Massimo; Lupidi, Giulio; Petrelli, Dezemona; Vitali, Luca A.; Papa, Fabrizio; Vittori, Sauro
Abstract Vepris macrophylla is an evergreen tree occurring in sub‐humid forest of Madagascar and traditionally used in the Island to treat several complaints as well as to prepare aromatic teas and alcoholic drinks. In the present work, the essential oil distilled from the leaves was analyzed for the first time by gas chromatography (GC‐FID) and gas chromatography/mass spectrometry (GC/MS). The major compounds were citral (56.3%), i.e., mixture of neral (23.1%) and geranial (33.2%), citronellol (14.5%), and myrcene (8.3%). The essential oil exhibited antimicrobial activity against S. aureus, P. aeruginosa, and C. albicans as determined by vapor‐diffusion assay, supporting the traditional use of the plant for preparing steam bath for the treatment of infectious diseases. The essential oil was evaluated for cytotoxic activity on human tumor cell lines by MTT (=3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl‐2H‐tetrazolium bromide) assay, showing inhibitory effects comparable to those of cisplatin, notably on MDA‐MB 231 (human breast adenocarcinoma) and HCT116 (human colon carcinoma) cell lines. Finally, the essential oil was also subjected to screening for its antioxidant activity and the free radical scavenging capacity.